United Republic of Tanzania - Public Expenditure and Financial Accountability Review 2009 - World Bank (World Bank, 2012)
The budget analysis section constitutes the 'core analyses of the Public Expenditure and Financial Accountability Review (PEFAR) 2009 report. The rapid budget analysis 2009 and the budget execution analysis 2009 are two key inputs into the report's core analysis. The report presents an overview of the main findings and key messages of the various sector and thematic reports carried out as part of the rapid budget analysis and budget execution analysis of the 2008-09 cycle. The analysis in this part of the report utilizes both budget estimates and actual expenditure data. The budget estimate data used are as originally approved by the Parliament, while the actual expenditure data used are as generated from the Integrated Financial Management System (IFMS). The actual expenditure data are in some parts complemented by the data downloaded from the 'logintanzania' website, especially data for Local Government Authorities (LGAs). As much as possible, the analysis is cast from a medium term perspective, with both budget estimates and actual spending data giving a three year trend or more in order to make some meaningful comparison. The last stage of the analysis in this part addresses the question of whether actual expenditures in 2008-09 were consistent with the original approved budget. It also examines the question of whether the budget achieves its stated impact on the ground, in terms of providing effective public services to the population in an equitable and efficient manner. In particular, the analysis of the execution of the budget in 2008-09, with a particular focus on the Ministries, Departments and Agency (MDA) development budget, is presented in this part. The analysis in this section continues by shedding some light on value audits conducted by the National Audit Office (NAO) in two key sectors, education and health.